Writing the Field Recording Sound, Word, Environment - Benson, Stephen (Edinburgh University Press, 2022)
Intervenes in contemporary debates about the relationship between literature and field recordingA field recording is any audio recording made outside of the studio. Such recordings have lately become important to contemporary musicians, sound artists and environmentalists. However, less attention has been given to the relation of sound, as manifested in the theory and practice of the field recording, to writing. The 11 essays collected here take the recent explosion of interest in field recording as the point of departure for an investigation of the sounded field in music and its relationship to literature and writing. Including seminal pieces on field thinking by John Berger and Lisa Robertson, Writing the Field Recording analyses contemporary text scores, histories, composer statements, critical literature, poetry and nature writing in the context of sound studies. Drawing on expertise from a range of backgrounds, including composers, musicians, poets and critics, the collection presents an inter-disciplinary exploration of the various registers in which the field recording is written, such as the essayistic, the creatively exploratory, the experimental and the philosophical alongside critical reflections on artistic practice.Key FeaturesFocuses on sound in relation to poetry, poetics and nature / landscape writingIncludes contributions from published poets Lisa Robertson, Carol Watts and Jonathan SkinnerIncludes the classic essay, 'Field', by John BergerAccompanying sound recordings made accessible via the Resources tab on the Edinburgh University Press website